1996
DOI: 10.1084/jem.183.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of murine tumors with tumor peptide-pulsed dendritic cells: dependence on T cells, B7 costimulation, and T helper cell 1-associated cytokines.

Abstract: SummaryAntigen presentation by host dendritic cells (DC) is critical for the initiation of adaptive immune responses. We have previously demonstrated in immunogenic routine tumor models that bone marrow (BM)-derived DC pulsed ex vivo with synthetic tumor-associated peptides, naturally expressed by tumor cells, serve as effective antitumor vaccines, protecting animals against an otherwise lethal tumor challenge (Mayordomo, J. I., T. Zorina, W.J. Storkus, C. Celluzzi, L. D. Falo, C.J. Melief, T. lldstad, W. M. K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
357
3
5

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 742 publications
(375 citation statements)
references
References 46 publications
10
357
3
5
Order By: Relevance
“…9,10 However, a powerful Th1-and CTLmediated response with production of IFN-␥ is thought to be necessary for the induction of antitumor immunity. 11 Whereas the two types of responses should be distinguishable based on the relative intensities of the cellular immune reactivity they induce, the strong immunogenicity of the foreign Ag used in the model studies tends to obscure these differences. They can be distinguished, however, on the basis of the isotype profile of the Ag-specific antibodies involved in the responses.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 However, a powerful Th1-and CTLmediated response with production of IFN-␥ is thought to be necessary for the induction of antitumor immunity. 11 Whereas the two types of responses should be distinguishable based on the relative intensities of the cellular immune reactivity they induce, the strong immunogenicity of the foreign Ag used in the model studies tends to obscure these differences. They can be distinguished, however, on the basis of the isotype profile of the Ag-specific antibodies involved in the responses.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several methods for induction of antitumor immunity by DCs have been investigated. The major methods for antigen loading into DCs are pulsing DCs with proteins or peptides extracted from tumor cells, [26][27][28] transfecting DCs with gene encoding tumor antigens, 29 fusing DCs with tumor cells 30,31 or culturing DCs with tumor cells. 32 Although some of these methods require primary culture of tumor cells from patients, primary cultures often fail to give the required number of cells, or expanded tumor cells often show different antigens from those expressed in tumor specimens due to changes in immunological characteristics over the long culture period for expansion.…”
mentioning
confidence: 99%
“…Unfortunately, the possible immunization of cancer patients using defined tumour antigens is limited at present to a handful of human tumour types in which candidates for tumour rejection antigens have been identified. In an attempt to overcome these major limitations, several investigators have recently reported induction of effective tumour immunity using DCs pulsed with unfractionated tumour-derived materials, acid eluted peptides or messenger RNA (mRNA) (Boczkowski et al, 1996;Nair et al, 1997a,b;Zitvogel et al, 1996). Hence, DC vaccine treatment might be extended to patients with a variety of solid tumours, provided that in vitro confirmation of tumourspecific CTL activity has been achieved.…”
Section: Intracellular Cytokine Expression By Tumour-specific T Cellsmentioning
confidence: 99%
“…Therefore, an alternative strategy for effective vaccination of tumour patients may be the use of unfractionated tumour-derived antigens such as whole tumour cells, peptides or proteins isolated from tumour cells. In this regard, effective tumour immunity in several murine tumour models has been induced using professional antigen presenting cells (pAPC) such as dendritic cells (DC) pulsed with unfractionated tumour-derived antigens in the form of peptides (Nair et al, 1997a;Zitvogel et al, 1996), cell sonicates (Nair et al, 1997b), or messenger RNA (mRNA) (Boczkowski et al, 1996).…”
mentioning
confidence: 99%